ANALISIS FAKTOR PENGHAMBAT IMPLEMENTASI SISTEM INFORMASI KESEHATAN UNTUK SENSUS HARIAN RAWAT INAP DI RSUD MUNTILAN - Yuliani, Resta Dwi (Politeknik Kesehatan Kemenkes Malang, 2023)
Background: Release of medical record information must be accompanied by a written permission of the patient and presentation of the contents must be signed by the treating doctor. Based on a preliminary study on April 2nd, 2018 in Bhayangkara Hospital Lumajang showed that, the patient’s waiting time in the release of the medical record information was 7 days. The purpose of this research is to analyze the obstacle factors for the release of information to third parties in Bhayangkara Lumajang Hospital. Subjects and Method: The method is qualitative with data collection techniques through interviews, observation, documentation and brainstorming. Results: The results of this research showed that there were factors that obstacle the release of information namely attitudes, behavior and expertise of health workers. The conditions of the registration room and medical record room, layout medical record room. Patient waiting time, physical evidence and patient perceptions that did not accordance. Conclusion: The obstacle factor for information release was the patient responsible doctor (DPJP) who is a partner doctor and doctor who was not in the place. The recommend effort to improve the release of information to third parties, Bhayangkara Hospital Lumajang must have permanent patient responsible doctor, and held a special rooms for information release. Suggestions from this research were making expedition book, socializing SOP and making information release information systems.